The Counsellor, an Instrument of Peace in a World of Confusion - Vanier, Jean Paul (Canadian Journal of Counselling and Psychotherapy, 1972)
In his keynote address to the CGCA Conference at Toronto in June, 1971, the author discussed the structuration of the personalities of both older and younger people in today's world, and gave his ideas on the counselor's role as a bridge between the world of adults and the world of the young. In addition to a technical role in which the counselor informs young people of possibilities for education and vocations, the counselor must also understand the young by sensing their suffering and identifying himself with them. He must believe in the young and make them realize that he values them -he must have found in himself an "interior liberty," having alliances with neither the forces of wealth, or of an egotistical, materialistic society, or social conventions, on the one hand, nor with the revolts and negative attitudes of youth on the other. The counselor must also seek to bring forth hope which will inspire new action and creativity. He must help the young to find projects that link their dreams to reality.Dr. Vanier concluded by remarking that the less young and the young together can surge forth to create communities of peace, of sharing, and of truth that "will be the foundation on which we can build, with the power of the Spirit of God, the community of men and nations living in peace and love".